Cover Feature: Adsorption‐Inhibition of Clathrate Hydrates by Self‐Assembled Nanostructures (ChemPhysChem 21/2021). Issue 21 (5th November 2021) - Soussana, Tamar Nicole; Weissman, Haim; Rybtchinski, Boris; Drori, Ran
Abstract : The Cover Feature presents tetrahydrofuran (THF) hydrates grown inside a microfluidic device in the presence of safranine O, a fluorescence dye, which binds to the surface of the crystal and inhibits further growth. The binding of safranine might be facilitated by self‐assembly into lamellar structures, imaged in aqueous solutions using cryo‐TEM. More information can be found in the Article by Ran Drori and co‐workers .